Bimbingan Bahasa Arab Tingkat Dasar Pada Masyarakat di Kelurahan Dermayu Kabupaten Seluma Bengkulu - Suryaningrat, Erwin; Rahman, Bobbi Aidi (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
A correct understanding of the contents of the Qur'an will give birth to a religious and religious society, that understanding will arise if there is an ability to understand the contents of the Qur'an which in fact speak Arabic, meaning that basic knowledge of Arabic is a necessity that cannot be ignored. But in the course of its history, Arabic was studied by Muslims only in the context of practical purposes, namely worship for example being able to read the Qur'an, so that when people are able to meet these targets, they no longer feel the need to learn Arabic, so that happens in the future is the stagnation and distortion of meaning in learning Arabic, which should be Arabic as the language of science only stops as a language of worship alone.